Exctraction of Foreign Body Aspiration in Children - Nisa Haska Maulina; Finny Fitry Yani (Science Midwifery, 2021)
Aspiration of foreign bodies by children can lead to serious illness and sometimes even death. It commonly ocurs in children younger than 3 years old, as they tend to put objects in their mouth. A local epidemiology study also revealed that among paediatric patients suffering from this condition, 73% were below the age of 3 years. Bronchoscopy is an endoscopic technique of visualizing the inside of the airways for diagnostic and therapeutic purposes. This case reported a 1 years and 3 months old boy with foreign body aspiration. Bronchoscopy with rigid brochoscope was performed electively. Patient was clinically improved after the bronchoscopy.